A fool there was [videorecording (DVD)] - Bara, Theda, 1885-1955; Jose, Edward; Swanson, Gloria, 1897-1983; Kipling, Rudyard, 1865-1936; Browne, Porter Emerson, 1879-1934 (Lost silent classics collection., 2010)
A cunning woman uses her irresistible charms to seduce and abandon a series of influential men. When one lover commits suicide on the deck of a luxury liner, she merely turns her gaze to another passenger, and leads him down a path to moral degradation and public scorn.